2015
DOI: 10.18632/oncotarget.5039
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of human cervical cancer proto-oncogene contributes to hepatitis B virus-induced malignant transformation of hepatocyte by down-regulating E-cadherin

Abstract: Hepatocellular carcinoma (HCC) is one of the most fatal human malignancies, Human cervical cancer proto-oncogene (HCCR) aberrantly expressed in a number of malignant tumors, including HCC. HCC is associated with Hepatitis B virus (HBV) infection in a large percentage of cases. To explore the regulation and function of HCCR expression in the development of HCC, we detected HCCR expression in HBV expressing hepatocytes. Results showed that the expression of HCCR was higher in HBV-expressing hepatocytes than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It has also been found that bladder cancer cell-derived exosomes can induce cell proliferation and inhibit tumor cell apoptosis in vitro in conjunction with upregulated expression levels of Bcl-2, but reduced expression levels of Bax and caspase-3 [ 29 ], which is in line with our current observations. Vimentin is a well-recognized metastasis marker [ 30 ], while E-cadherin is known to repress the invasion and metastasis of epithelial cells [ 31 ]. Additionally, CAF-secreted exosomes have been found to reinforce metastasis and chemoresistance by enhancing EMT in colorectal cancer cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that bladder cancer cell-derived exosomes can induce cell proliferation and inhibit tumor cell apoptosis in vitro in conjunction with upregulated expression levels of Bcl-2, but reduced expression levels of Bax and caspase-3 [ 29 ], which is in line with our current observations. Vimentin is a well-recognized metastasis marker [ 30 ], while E-cadherin is known to repress the invasion and metastasis of epithelial cells [ 31 ]. Additionally, CAF-secreted exosomes have been found to reinforce metastasis and chemoresistance by enhancing EMT in colorectal cancer cells [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…vimentin expression is a late event in EMT and is preceded by a loss of epithelial features, which leads to the upregulation of mesenchymal genes [45]. E-cadherin, which promotes cell-cell contact and suppresses the malignant invasion and metastasis of epithelial cells, is associated with the invasiveness of HCC cells [46]. The loss of E-cadherin enables metastasis by disrupting intercellular contacts, an early step in metastatic dissemination [29].…”
Section: Discussionmentioning
confidence: 99%
“…The EMT is a crucial mechanism of tumor cell invasion and cancer metastasis, by which epithelial cells obtain mesenchymal fibroblast-like properties [ 35 ]. Vimentin is a well-recognized metastasis marker [ 36 ], while E-cadherin could repress the invasion and metastasis of epithelial cells [ 37 ]. EMT is a great contributor to the CC cell chemotherapy and radiotherapy resistance; thus, inhibiting EMT improves the survival rate of CC patients by sensitizing the CC cells to radiotherapy and drugs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%